Braconid and ichneumonid (Hymenoptera) parasitoid wasps of Lepidoptera from the Maltese Islands - Mifsud, David; Farrugia, Lucia; Shaw, Mark R. (Zootaxa, 2019)
Fourteen species of Ichneumonidae are here recorded from the Maltese Islands. Of these, all were reared from Lepidoptera hosts with the exception of Netelia (Paropheltes) inedita (Kokujev) which was collected from a malaise trap. Of these, the following species (or genera) are here reported for the first time from the Maltese Islands: Chirotica meridionalis Horstmann, Gelis carbonarius (de Stefani), G. exareolatus (Fӧrster), G. seyrigi Ceballos, Glypta sp., Meloboris sp., Netelia (Paropheltes) inedita (Kokujev), Ophion obscuratus Fabricius and Orthizema sp. Twenty-five species of Braconidae are also here reported from Lepidoptera hosts with the exception of Homolobus (Phylacter) meridionalis van Achterberg which was collected from a malaise trap. Of these, the following species (or genera) represent new records for the Maltese Islands: Apanteles metacarpalis (Thomson), Ascogaster sp., Clinocentrus excubitor (Haliday) [previously misidentified as C. exsertor (Nees) by Papp (2015)], Cotesia vestalis (Haliday) [previously misidentified as C. ruficrus (Haliday) by Papp (2015)], Dolichogenidea britannica (Wilkinson), Homolobus (Phylacter) meridionalis van Achterberg, Iconella ? meruloides (Nixon), Lysitermus tritoma (Bouček), Lysitermus suecius (Hedqvist), Microgaster messoria Haliday, Meteorus pulchricornis (Wesmael), Pholetesor circumscriptus (Nees) [previously misidentified as P. bicolor (Nees) by Papp (2015)] and Spathius pedestris Wesmael. Thus previous records of Clinocentrus exsertor and Pholetesor bicolor from Malta were found to be based on misidentifications and are here excluded from the braconid fauna of Malta. Maltese records of Cotesia abjecta (Marshall) and Cotesia jucunda (Marshall) by Papp (2015) were found to be misidentifications and should both refer to C. glomerata (Linnaeus). Thus, both Cotesia abjecta and Cotesia jucunda are also here removed from the braconid fauna of Malta. The record of Cotesia tibialis (Curtis) by Papp (2015) was also based on a misidentification and should be attributed to C. ruficrus (Haliday). Thus, C. tibialis is also removed from the braconid fauna of Malta.